Addition of Aegilops biuncialis chromosomes 2M or 3M improves the salt tolerance of wheat in different way - Darko, Eva; Khalil, Radwan; Dobi, Zsanett; Kovács, Viktória; Szalai, Gabriella; Janda, Tibor; Molnár, István (Scientific reports, 2020)
Aegilops biuncialis is a promising gene source to improve salt tolerance of wheat via interspecific hybridization. In the present work, the salt stress responses of wheat-Ae. biuncialis addition lines were investigated during germination and in young plants to identify which Aegilops chromosomes can improve the salt tolerance of wheat. After salt treatments, the Aegilops parent and the addition lines 2M, 3M and 3M.4BS showed higher germination potential, shoot and root growth, better CO2 assimilation capacity and less chlorophyll degradation than the wheat parent. The Aegilops parent accumulated less Na in the roots due to an up-regulation of SOS1, SOS2 and HVP1 genes, while it contained higher amount of proline, fructose, glucose, galactose, maltose and raffinose. In the leaves, lower Na level was accompanied by high amount of proline and increased expression of NHX2 gene. The enhanced accumulation of sugars and proline was also observed in the roots of 3M and 3M.4BS addition lines. Typical mechanism of 2M addition line was the sequestration of Na into the vacuole due to the increased expression of HVP1 in the roots and NHX2 in the leaves. These results suggest the Aegilops chromosomes 2M and 3M can improve salt tolerance of wheat in different way.
Keywords: hybridizace genetická; Hybridization, Genetic; Salt Tolerance; Triticum; Chromosomes, Plant; Sodium; pšenice; Aegilops; Germination; sodík; chromozomy rostlin; tolerance k soli; klíčení